(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Concrete is the main component in construction of civil infrastructure. However, deformation in concrete such as crack or void may occur either on its early stage or during its usage. Hence, concrete evaluation is a need in determining its strength and quality status. Direct Ultrasonic Pulse Velocity (UPV) method is the most common non-destructive measurement adopted to assess the condition of concrete structure. However, problems arise when there is limited accessible surface to probe the ultrasonic transducers. Hence, this project is undertaken to analyse ultrasonic NDT by utilising different arrangement of sensors on tested concrete. The simulation of the homogenous and non-homogenous concrete system will be done by using COMSOL Multiphysics software. The output signal obtained from the simulation is used for the image reconstruction by using the sensitivity mapping technique. The results are then validated by assessing the actual model of concrete structure using direct, indirect, and semi-direct UPV probing in order to get the exact location of defects. Preliminary result shows that proposed method can help to improve the defects determination in concrete structure.